(adsbygoogle = window.adsbygoogle || []).push({}); 1. The problem statement, all variables and given/known data

Prove that summation k^3 from k=1 to k=n is equal to (summation of k from k=1 to k=n)^2.

2. Relevant equations

Induction Principle

3. The attempt at a solution

It is true for k=1, so we must assume it is true for k=n-->then prove true for k=n+1.

Where do I go from here?

**Physics Forums | Science Articles, Homework Help, Discussion**

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Homework Help: Induction Principle

**Physics Forums | Science Articles, Homework Help, Discussion**